2021
DOI: 10.33024/jmm.v4i3.2498
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kepatuhan Minum Obat Antiretroviral Pasca 6-12 Bulan Dengan Kadar Viral Load Pada Lelaki Seks Lelaki (Lsl) Yang Terinfeksi Human Immunodeficiency Virus (Hiv) Di Bandar Lampung Tahun 2019

Abstract: Human Immunodeficiency Virus (HIV) adalah suatu retrovirus yang menyerang sistem kekebalan tubuh. Kepatuhan minum obat antiretroviral merupakan keharusan dalam menurunkan jumlah virus dalam darah. Pada komunitas Lelaki Seks Lelaki (LSL) di Bandar Lampung yang terinfeksi HIV masih banyak yang tidak patuh dalam meminum obat antiretroviral itu sendiri. Salah satu cara untuk mengetahui keberhasilan pengobatan antiretroviral dapat dilakukan pemantauan terapi yaitu dengan tes viral load. Mengetahui hubungan antara k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The factors that support the success of therapy with antiretrovirals are compliance, self-motivation, services, and social support from both the family and the environment. 2 ARV treatment requires PLWHA to comply and carry out regular treatment. Violations in taking medication can be fatal and can even lead to failure in the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…The factors that support the success of therapy with antiretrovirals are compliance, self-motivation, services, and social support from both the family and the environment. 2 ARV treatment requires PLWHA to comply and carry out regular treatment. Violations in taking medication can be fatal and can even lead to failure in the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research conducted by [7], HIV viral load testing can show results that are not detected in people with HIV. Meanwhile, from research that has been conducted by [8], it was found that the rapid test had a positive predictive value and a negative predictive value of 100% so the examination obtained results by reality by 100%.…”
Section: Introductionmentioning
confidence: 99%